PENANGGULANGAN PENYAKIT GETAH KUNING DALAM UPAYA PENINGKATAN KUALITAS DAN KUANTITAS PRODUKSI MANGGIS - Kusmiyarti, T.B.; Roni, N.G.K.; Kusmawati, T. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2018)
The purpose of this community service activities is to increase the quality and quantity of production of mangosteen as the main export commodities through: (improvement of mangosteen cultivation and prevention of disease lymph mangosteen fruit; The method adopted to achieve these goals is through education, training, simulation science and technology, mentoring, and design appropriate technology applied. Approaches used include: transfer tenologi appropriate to the community and the development of entrepreneurial insight, Science and technology dissemination activities through this community service programs going well demonstrated by their active participation and adoption of science and technology. Active participation of partners in all activities of dissemination of technology is quite high at 73.0% adoption of science and technology capability and initiative partners to produce products independently is quite high at 80%.